Modal must in Philippine editorials a corpus-based study - Morales, Rodrigo Concepcion (Philippine Journal of Linguistics, 2015)
The present study examines the semantic functions and the dominant verb-phrase structure of the modal must under the category of printed written texts of persuasive writing in press editorials found in the Philippine component of the International Corpus of English (ICE-PHI) compiled by Bautista, Lising, and Dayag (1999). Moreover, the study aims to determine whether the modal must conforms to or deviates from the standard modal usage in American English. A total of 36 texts were analyzed for the study with approximately less than 32,000 words. The findings revealed that the dominant verb-phrase structure of the modal must is must + base form of the verb, which is favored by Filipino press editorial writers because of the seemingly overtly authoritative tone of the modal must. Overall, the results of the present study further confirm Gustilo’s (2011) findings that the modal must in Philippine editorials maintains its conformity to the standard modal usage in American English. Based on the study results, a number of pedagogical implications are provided for ESL/EFL instruction and for future research.